Atividade antimicrobiana de barbatimão Stryphnodendron adstringens (Martius) Coville em agentes causadores da mastite - Diego Bardal (2011)
Medicinal plants re-emerged as options to existing protocols to treat diseases. In this context, it was investigated the antimicrobial activity in vitro of aqueous extract of Stryphnodendron adstringens (Martius) Coville, Leguminosae-Mimosoidae, compared to micro-organisms associated with bovine mastitis. They used standard strains (ATCC) of Staphylococcus aureus (6538), Escherichia coli (8739), Streptococcus pyogenes (19615), Pseudomonas aeruginosa (9027) and Candida albicans (10 231). To stem-bark of barbatimao, we proceeded to the identification and botanical confirmation, after comminuted and standardized they held the physical chemistry screening and extraction of bioactive by turbo-extraction in hydromethanol mixture (1:1 w/v) with S. adstringens. After fractionationed destilation and recomposition was obtained the aqueous extract with 328.18 mg/m and 38.81% of total tannins, which were used in tests of broth macrodilution and disk of agar diffusion. It was investigated the antimicrobial activity by inhibitory concentrations (MIC) and bactericidal/fungicidal (CBM/CFM) minimum of the extract. In a completely randomized design were carried out scores of colonies viable in triplicate for each micro-organism at times of 0, 6, 12, 18 and 24 h, compared to concentrations of 1, 5, 25, 50 and 75 mg/m of extract of barbatimao. They were analyzed by ANOVA with Tukey test (p 0.01); the data of the macrodilution and of the diffusion in factorial model double and triple, respectively. It was used regression (p 0.01) to construct the graphics of kinetics of inactivation of the microbial growth. The MICs (mg/m) compared to aqueous extract of S. adstringens were 75, 1, 5 to 25 and 25, respectively, for S. aureus, S. pyogenes, P. aeruginosa and C. albicans. The aqueous extract of barbatimao did not show antibacterial effect on E. coli. The CBM in the presence of the extract of S. adstringens were 25 mg/m for S. pyogenes and P. aeruginosa and 50 mg/m for C. albicans. The real barbatimao showed antimicrobial effect against pathogens causing mastitis. Therefore, further studies should be undertaken for the future use in vivo.